Overcoming legal formalism and the protection of the Slovak Republic Constitutionalism - J. Ondrová; M. Úradník (Аналітично-порівняльне правознавство)
The principles are considered the basic ones as they constitute the contradistinguished component-part between the lawful state and another state establishment. However, it would be naive to think and to rely on the reality that the only creation of the basic principles is sufficient for the further legal state “life”. Therefore, it is needful to implement the legal state principles into the everyday decision-making activities of the public power bodies, and at the same time to maximize the safeguarding of their protection while refusing the exclusive authority of lawmaker.